Sources of DNA for detecting B cell monoclonality using PCR. Issue 6 (June 1994) - Diss, T C; Pan, L; Peng, H; Wotherspoon, A C; Isaacson, P G
Abstract : AIMS–To evaluate the polymerase chain reaction (PCR) demonstration of clonal immunoglobulin heavy chain gene rearrangements using routinely prepared, unstained, and stained formalin fixed, paraffin wax embedded tissue samples. METHODS–Extracts from (a) fresh frozen tissue samples, (b) unstained, and (c) haematoxylin and eosin stained formalin fixed, paraffin wax embedded 5 microns tissue sections from 42 cases of low grade B cell lymphoma, all shown to be monoclonal by Southern blot analysis, were analysed using PCR. Two regions of the variable segment of the immunoglobulin heavy chain gene were amplified (framework 2 to joining region [Fr2/JH] and framework 3 to joining region [Fr3/JH]). Twelve samples of reactive lymphoid tissue were studied as controls. Products from each case were directly compared on polyacrylamide gels. RESULTS–Using both primer combinations, monoclonality was detected in 38 of 42 (90%) cases using fresh material, 37 of 42 (88%) using unstained paraffin wax embedded samples, and in 35 of 42 (83%) cases using haematoxylin and eosin stained sections. No false positive results attributable to fixation, processing, or staining were identified, although the efficiency of amplification using the Fr2/JH primers was significantly reduced. CONCLUSIONS–PCR determination of B cell clonality using paraffin wax embedded material is sufficiently sensitive and reliable for use as a routine diagnostic adjunct to conventional morphological and immunocytochemical assessment of lymphoproliferative disease.